THE IMPACT OF LEADERSHIP AND CULTURE OF ORGANIZATION TO EMOTIONAL INTELLIGENCE BY TRAINING OF PT. XYZ - Bahyudi Bahyudi; Tjiptogoro Dinarjo Soehari (Akademika, 2020)
Modern retail business competition is increasingly fierce today, making business competitors continue to improve services and development in order to compete in the current era, one of which is PT. XYZ, which is engaged in supermarket retailing, continues to develop its chain of stores in several regions in Indonesia and improve the quality of its leaders. This study discusses and analyzes the leadership and culture of emotional intelligence that is by training. The study was taken from several employees of PT. XYZ during August, September and October. The sampling method used was purposive sampling, from a population of 161 PT. XYZ meets the criteria for being a sample. The analytical method used in this study is Structural Equitional Modeling with Lisrel. The results showed that leadership had a positive and significant effect on training. The effect of training on emotional intelligence has a positive and significant effect on emotional intelligence. The influence of organizational culture on emotional intelligence also has a positive and significant effect on emotional intelligence. Organizational culture is the most influential variable on emotional intelligence.